RESEARCH OF THE WEAR RESISTANCE OF ELECTRO-SPARK COATINGS UNDER ABRASIVE CONDITIONS - Skvortsov, Oleksandr; Mikosianchyk, Oksana (Problems of Friction and Wear, 2023)
The reasons for the destruction of parts of the friction units of aircraft and ground aviation equipment, which are made of iron-based alloys, were analyzed, and it was established that during operation, various processes develop on their working surfaces, namely: abrasive wear, seizure, fretting - corrosion, fatigue wear. The analysis of modern technological methods of surface strengthening of machine parts was carried out, the prospects of electrospark alloying of iron-based alloys were determined. Research on the wear resistance of coatings was carried out using a complex methodology, which includes metallographic, electron microscopic, durometric, and other methods of analysis of physical and mechanical methods. The influence of electrode materials on the wear resistance of ESD coatings has been established. Practical recommendations for surface strengthening of parts of automatic transmission systems operating under conditions of abrasive wear are indicated.